Can nasal septum deviation be one of the factors affecting diabetic retinopathy? - Yaşar, Erdoğan; Kayabasi, Serkan (Journal of Surgery and Medicine, 2020)
Aim: Information on the extraocular causes of diabetic retinopathy is limited. Therefore, when researching etiology in a patient with diabetic retinopathy, if glucose, blood pressure and cholesterol are normal, other reasons must be investigated. Our aim was to evaluate the effect of nasal septum deviation (NSD) on the presence and severity of diabetic retinopathy in patients with diabetes mellitus. Methods: This prospective case-control study included 100 eyes of 50 patients with only diabetes mellitus (DM+ NSD-, control group) and 120 eyes of 60 patients with DM and nasal septum deviation (DM+NSD+, NSD group). After evaluation of NSD patients using a nasal obstruction symptom evaluation scale (NOSE scale), 22 patients were classified as mild, 21 as moderate, and 17 as severe. Anterior segment and dilated fundus examinations were performed in all patients. Diabetic retinopathy (DR) was classified as mild, moderate, and severe non-proliferative DR and proliferative DR (PDR). Results: The mean age of patients in the NSD and control groups was 58.7 (15.2) years (range: 41–69) and 59.6 (8.1) years (range: 44–67), respectively. The prevalence of DR and PDR were 70% (n=14) and 30% (n=6), respectively, in the severe NSD group (P=0.045 and P=0.035, respectively). The relationship between PDR and other factors in patients with NSD were evaluated, and a correlation was detected with DM duration (P=0.024, OR=1.272), HbA1c (P=0.032, OR=3.085), and NOSE scale severity (P=0.040, OR=2.566). Conclusion: The results of the present study show an increased risk of DR and PDR in patients with severe NSD. In addition to other risk factors in PDR etiology, NSD should also be considered.